ALS and SAD-like nicotinic acetylcholine receptor subunit genes are widely distributed in insects. - Sgard, F.; Obosi, L.A.; King, L.A.; Windass, J.D. (Insect Molecular Biology, 1993)
Segments of nicotinic acetylcholine receptor alpha subunit genes have been isolated from a panel of insect species by polymerase chain reaction, using degenerate oligonucleotide primers designed to recognize conserved regions of the Drosophila melanogaster ALS and SAD genes. The amplified segments encode elements of typical alpha-subunits anticipated to play roles in ligand binding and ion channel formation. Each is also clearly either ALS or SAD-like. The predicted protein sequences display extremely high levels of conservation (over 85% for each subtype) even though derived from very distantly related insect species.